Pengembangan Media Video Modeling untuk Manajemen Perilaku Anak Autis dalam Berinteraksi Sosial - Mahfudz Mahfudz; Fathir Fathir; Syafa’at Syafa’at; Widajati Widajati (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This think about points to create and assess the adequacy of video modeling media in behavior administration and the improvement of social interaction aptitudes in children with extreme introvertedness. The inquire about utilized a subjective approach with a case consider plan, including two extremely introverted children who shown troubles in social interaction. The investigate strategy was conducted in a few stages, extending from issue distinguishing proof to the assessment of media execution results. Information were collected through perceptions, interviews with instructors and guardians, and documentation. The discoveries uncovered that video modeling media had a positive affect on children's social behavior, such as enhancements in welcoming abilities, eye contact, and support in gather exercises. The primary subject appeared discernible advance from the third session, whereas the moment subject illustrated slower but still critical improvement. Supporting components for the victory of the intercession included video redundancy, clear behavioral models, and dynamic inclusion of facilitators all through the mediation prepare. These discoveries fortify the idea that visual media designed agreeing to desires of children with extreme introvertedness can serve as a commonsense, adaptable, and viable mediation in both uncommon and comprehensive instruction settings. This think about too contributes significantly to the advancement of scientifically-based guidelines media that's responsive to the person characteristics of children with uncommon needs.